The consolidated assistance program: Reforming welfare by synchronizing public assistance benefits - Oren M. Levin-Waldman (Levy Economics Institute of Bard College, 1995)
In this brief, Oren M. Levin-Waldman examines the structure of existing welfare programs and concludes that the current array of benefits could be synchronized and consolidated to create a new system that would provide economic incentives to work. He suggests combining elements of the earned income tax credit (EITC) and current welfare programs into one program, a consolidated assistance program (CAP). Levin-Waldman argues that a program composed of an assistance component (with one set of benefits for working parents and a different set for nonworking parents) and a child support component could be designed to assure minimal subsistence to those unable to work while providing incentives for those on welfare to work without, in effect, penalizing them for getting off welfare. Such a program would reform welfare more expeditiously than a plan that would simply expand the EITC or put a time limit on welfare benefits. Moreover, such a plan would not necessarily add to the national budget deficit.
Keywords: 330